Emerging market multinationals' firm-specific advantages, institutional distance, and foreign acquisition location choice. Issue 5 (October 2020) - James, Barclay E.; Sawant, Rajeev J.; Bendickson, Joshua S.
Highlights: Institutional Distance (ID), emerging market multinational enterprise (EMNE), firm-specific advantage (FSA). ID is positively related to EMNE foreign acquisition location choice. EMNE FSAs shaped by home-country conditions reduce the positive effect of ID on foreign acquisition location choice. EMNE FSAs shaped by EMNE investment choices increase the positive effect of ID on foreign acquisition location choice. Abstract: How do emerging market multinational enterprises' (EMNEs') firm-specific advantages (FSAs) drive their foreign acquisition location choice? We theorize EMNE FSAs as important contingencies influencing the effect of institutional distance (ID) on EMNE foreign acquisition location choice. As a baseline main effect, we expect ID to positively influence EMNE location choice, as well-developed institutionally distant host-country environments are attractive to EMNEs. This effect is reduced by EMNE FSAs shaped by home-country conditions, such as success in navigating institutional voids and superior human resource management, which are more competitive in institutionally closer countries. Conversely, this effect is heightened by EMNE FSAs shaped by investment choices for knowledge and for international venturing. Based on analyses of 278 EMNE acquisitions by EMNEs from nine emerging markets, our findings largely support our hypotheses. Our study extends research on EMNE FSAs, which often have been compared only with those of developed-country multinational enterprises.